ELECTROCONVULSIVE THERAPY AS A LAST RESORT IN TREATING SEVERE DEPRESSION AND BIPOLAR DISORDER - JYOTI SISODIYA (International Journal of Multidisciplinary Research and Studies, 2021)
Treatment of bipolar depression (BD-D) continues to represent a significant unmet need. On average, patients with bipolar disorder (both bipolar I (BD-I), defined by the presence of mania, and bipolar II (BD-II), defined by presence of hypomania) who are treated according to established guidelines are euthymic only about 50% of the time. Further, patients with bipolar disorder spend three times more days depressed than manic or hypomanic. Depression, therefore, represents a quite common mood state among patients with bipolar disorder. This is particularly worrisome as BD-D significantly impacts an individual’s psychosocial functioning, with impairments in work, social and family life. Suicides, which are disproportionately high in bipolar disorder, predominantly occur in the depressive state. Furthermore, BD-D is the major contributor to disability associated with the illness. Despite these serious adverse impacts of bipolar disorder, over 50% of patients with bipolar disorder are at least partially non-adherent to medications. Many factors contribute to non-adherence, including lack of psychoeducation and insight into the chronic and episodic nature of the disease.Additionally, a significant number of patients experience intolerable side effects of medications.